Opioid Demand Before and After Anterior Cruciate Ligament Reconstruction. (November 2017) - Anthony, Chris A.; Westermann, Robert W.; Bedard, Nicholas; Glass, Natalie; Bollier, Matt; Hettrich, Carolyn M.; Wolf, Brian R.
Background: Surgeons and health care systems have received a call to action in an effort to curtail the current opioid epidemic. Purpose: To (1) define the natural history of opioid demand after anterior cruciate ligament reconstruction (ACLR), (2) consider how filling preoperative opioid prescriptions affects opioid demand after ACLR, and (3) evaluate the effect of additional procedures during ACLR and patient age on postoperative opioid demand. Study Design: Cohort study; Level of evidence, 3. Methods: ACLRs performed in the Humana database between 2007 and 2014 were identified using Current Procedural Terminology code 29888. Patients were considered preoperative opioid users if they had filled an opioid prescription in the 3 months preceding surgery. Patients were defined as "chronic" opioid users if they had filled a prescription preoperatively at 1 to 3 months from surgery. Further categorization was performed by identifying patients who only underwent ACLR with no other procedures, those who underwent ACLR with meniscus repair, those who underwent ACLR with meniscectomy, and those who underwent ACLR with microfracture. Categorization by age was also performed. The relative risk (RR) of postoperative opioid use was calculated, and 95% CIs were determined. Results: Over the course of the study period, 4946 ACLRs were performed. At 3 months after their procedure, 7.24% of patients were still filling opioid prescriptions. At 9 and 12 months postoperatively, 4.97% and 4.71% of patients, respectively, were still filling opioid prescriptions. Nearly 35% of patients (1716/4946) were filling opioid pain prescriptions in the 3 months before ACLR. Those filling preoperative opioid prescriptions were 5.35 (95% CI, 4.15-6.90) times more likely to be filling opioid prescriptions at 3 months after ACLR than nonusers (15.38% vs 2.88%, respectively). Those filling opioid prescriptions chronically before surgery were at a 10.50 (95% CI, 7.53-14.64) times increased risk of filling postoperative opioid prescriptions at 5 months. At 5 months postoperatively, patients undergoing ACLR with microfracture had a 1.96 (95% CI, 1.34-2.87) increased risk of filling opioid prescriptions compared with ACLR alone, 2.38 (95% CI, 1.48-3.82) increased risk compared with ACLR with meniscus repair, and 1.51 (95% CI, 1.04-2.19) increased risk compared with ACLR with meniscectomy. Patients younger than 25 years of age had an increased risk of filling opioid prescriptions after ACLR at all time points of the study. Conclusion: Opioid demand after ACLR dropped significantly in the vast majority of patients by the third postoperative month. Surprisingly, 35% of patients undergoing ACLR were observed to be using opioid medication preoperatively, and this study found preoperative opioid use to be a strong predictor of postoperative opioid demand with a 5- to 7-fold increased risk in this patient population. Patients who were filling opioid prescriptions 1 to 3 months from their surgical date were at the highest risk for postoperative opioid utilization. Patients undergoing ACLR with microfracture were at an increased risk of filling opioid prescriptions. Patients less than 25 years of age were at an elevated risk of filling opioid prescriptions at all time points postoperatively.